2013
DOI: 10.3138/jcfs.44.5.557
|View full text |Cite
|
Sign up to set email alerts
|

European Men’s Use of Parental Leave and Their Involvement in Child Care and Housework

Abstract: Although parental leave has long formed part of traditional labor relations, it was not until the nineteen seventies that it began to be regarded in some Scandinavian countries as a way ofi balancing work and family life as well as of enhancing gender equality (Duvander,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
2
30
0
2
Order By: Relevance
“…Nevertheless, it seems to be a phenomenon established firmly enough and one treated with sufficient sensitivity by society. In this sense reference is often made to a "new father" (Yeung et al, 2001) or "superdads" (Kaufman, 2013); of a "new masculinity" (Connell, 2014); of a "new culture of fatherhood" (Wall and Arnold, 2007;Meil, 2013); or of a "involved fathering" (Gatrell et al, 2015). This typology of father (found mostly among young males with high levels of education and egalitarian gender attitudes) may not be the mainstream but it is emerging.…”
Section: Artículo / Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, it seems to be a phenomenon established firmly enough and one treated with sufficient sensitivity by society. In this sense reference is often made to a "new father" (Yeung et al, 2001) or "superdads" (Kaufman, 2013); of a "new masculinity" (Connell, 2014); of a "new culture of fatherhood" (Wall and Arnold, 2007;Meil, 2013); or of a "involved fathering" (Gatrell et al, 2015). This typology of father (found mostly among young males with high levels of education and egalitarian gender attitudes) may not be the mainstream but it is emerging.…”
Section: Artículo / Articlementioning
confidence: 99%
“…The arguments related to gender equality are a fundamental line in the justification of these policies of parental leave reform. The literature on this issue shows that men tend to respond well to the introduction of well paid and non-transferable leaves (Duvander and Johansson, 2012;Ekberg et al, 2013;Escot et al, 2014;Castro and Pazos, 2016); meanwhile, taking longer leaves may promote greater subsequent involvement of the father in childcare (Duvander and Jans, 2008;Haas and Hwang, 2008;Kotsadam and Finseraas, 2011;Meil, 2013;Arnalds et al, 2013;Fernández-Cornejo et al, 2016a); and these resulting higher levels of shared responsibility in the care of babies and young children may result in mothers making fewer professional sacrifices in order to care for the child (the motherhood penalty would be lower).…”
Section: Artículo / Articlementioning
confidence: 99%
See 1 more Smart Citation
“…A large body of research relates to father involvement in care work and specific phases of fatherhood. It has been shown that father involvement depends on various influences that range from gendered expectations and attitudes towards the division of labour (Shirani et al 2012;Poortman/van der Lippe 2009;Baxter 2000), embodied experiences and differences (Doucet 2009(Doucet , 2013Draper 2003) to parental leave policies (Saraceno/Keck 2011;Brandth/Kvande 2009;Meil 2013;Schmidt et al 2015) and parents' occupation and working hours (Norman et al 2013;McGill 2014). Moreover, empirical evidence has shown that it is crucial for understanding father involvement to include the pre-and postnatal phases in the analysis.…”
Section: Father Involvement At the Transition To Parenthood -State Ofmentioning
confidence: 99%
“…New paternity ideals arise, which praise the bond between fathers and children, and their frequent and early interaction (Bonino ). Some authors point out that the evolution of social policies for gender equality and specifically paternity leaves for birth are enabling a more active participation of men in the domestic sphere in several European countries (Meil ).…”
Section: Introductionmentioning
confidence: 99%